TACTILISM IN THE CINEMATOGRAPHIC WORK OF ŠVANK-MAJER - Dabert, Dobrochna (Porównania, 2015)
The article focuses on tactilism as the artistic idea in the art of Jan Švankmajer’s animation films The idea of tac-tilism as presented by Švankmajer in numerous theoretical papers is analysed and confronted with his artistic practice. According to the Prague-based artist, by means of the sense of touch one can reach the subconscious, unrecognised or forgotten experiences, impressions, memories and activate the imagination in a way that is inaccessible to other senses. In the search for the possibility to transfer the sense of touch into the art of film animation, the artist pays particular attention to means of artistic expressions including macro details in motion.